New insights into the relationship between the average nucleotide identity and the digital DNA–DNA hybridization values in the genus Amycolatopsis and Amycolatopsis cynarae sp. nov., a novel actinobacterium from the rhizosphere soil of Cynara scolymus, and proposal of Amycolatopsis niigatensis as a synonym of Amycolatopsis echigonensis based on comparative genomic analysis - Deng, Aihua; Fu, Li; Mo, Ping; Zheng, Yaxi; Tang, Ting; Gao, Jian (Frontiers in Microbiology, 2024)
At present, it is widely believed that a 95–96% average nucleotide identity (ANI) value is equivalent to a 70% digital DNA–DNA hybridization (dDDH) value in the prokaryotic taxonomy. However, in the present study, comparative genome analysis of 29 pairs of Amycolatopsis type strains revealed that a 70% dDDH value did not correspond to a 95–96% ANI based on the MuMmer ultra-rapid aligning tool (ANIm) but approximately corresponded to a 96.6% ANIm value in the genus Amycolatopsis. Based on this corresponding relationship, phenotypic and chemotaxonomical characteristics, as well as phylogenetic analysis, an actinobacterial strain HUAS 11-8T isolated from the rhizosphere soil of Cynara scolymus, was subjected to a polyphasic taxonomic characterization. Based on EzBioCloud alignment, it was found that strain HUAS11-8T had the 16S rRNA gene similarities of 99.78% with A. rhizosphaerae JCM 32589T, 97.8% with A. dongchuanensis YIM 75904T, and < 97.8% sequence similarities to other Amycolatopsis species. Phylogenetic analysis of 16S rRNA gene sequences and whole-genome sequences revealed that strain HUAS 11-8T was closely related to A. rhizosphaerae JCM 32589T. ANIm and dDDH values between strains HUAS 11-8T and A. rhizosphaerae JCM 32589T were 96.3 and 68.5%, respectively, lower than the 96.6 and 70% thresholds recommended for the delineation of a novel Amycolatopsis species. Consequently, strain HUAS 11-8T should represent a novel Amycolatopsis species, for which the name Amycolatopsis cynarae sp. nov. (type strain HUAS 11-8T = MCCC 1K08337T = JCM 35980T) is proposed. Furthermore, based on comparative genomic analysis and rule 42 of the Prokaryotic Code, we propose that Amycolatopsis niigatensis is a later heterotypic synonym of Amycolatopsis echigonensis.